Assessment and Pollution Characteristics of Heavy Metals in Soil of Different Functional Areas in Luoyang - Liu, Ya-Na; Zhu, Shu-Fa; Wei, Xue-Feng; Miao, Juan; Zhou, Ming; Guan, Feng-Jie (Huanjing kexue, 2016)
The residential areas, science and education areas, urban green lands, commercial districts, urban arterial roads, industrial zones and urban and rural junction districts in seven different functional zones of Luoyang City were taken as research subjects, and sixty-three soil samples were gathered. The concentrations of soil heavy metals were measured and their pollution levels were evaluated by single pollution index and Nemerow complex pollution indices. The ecological risks of soil heavy metals were discussed with Hakanson potential ecological risk index (RI) and their geneses and sources were indicated by the principal component analysis (PCA). The results showed that the average level of all heavy metals exceeded the background values of Henan Province. The pollution degree of single gene index was in the following order:Cd> Zn> Pb> Cu> Ni> Cr. Nemerow complex pollution indices indicated heavy metals had the highest concentration and the heaviest pollution in industrial zones. A single heavy metal potent